2022
DOI: 10.3390/cancers14061365
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Sparing of Organs at Risk with Modern Proton Therapy in Lung Cancer, but Altered Breathing Patterns Can Jeopardize Target Coverage

Abstract: Enhancing treatment of locally advanced non-small cell lung cancer (LA-NSCLC) by using pencil beam scanning proton therapy (PBS-PT) is attractive, but little knowledge exists on the effects of uncertainties occurring between the planning (Plan) and the start of treatment (Start). In this prospective simulation study, we investigated the clinical potential for PBS-PT under the influence of such uncertainties. Imaging with 4DCT at Plan and Start was carried out for 15 patients that received state-of-the-art inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In addition, we considered that since the mean absolute dose differences were 0.1 GyRBE for both techniques, the OAR doses in the SFUD and IMPT plans might not be signi cantly affected by the interplay effect. Moreover, when comparing the OAR doses with both techniques, the IMPT plan could considerably spare the doses because robust optimization tends to shrink the irradiation volume more than the conservative beam-speci c margin concept, which is consistent with several previous studies [41][42][43]. However, it is worth noting that the dose constraints for the OARs were not applied in the optimization process in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, we considered that since the mean absolute dose differences were 0.1 GyRBE for both techniques, the OAR doses in the SFUD and IMPT plans might not be signi cantly affected by the interplay effect. Moreover, when comparing the OAR doses with both techniques, the IMPT plan could considerably spare the doses because robust optimization tends to shrink the irradiation volume more than the conservative beam-speci c margin concept, which is consistent with several previous studies [41][42][43]. However, it is worth noting that the dose constraints for the OARs were not applied in the optimization process in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the OAR doses, there were no statistically signi cant differences between SD and 4DDD, except for the esophagus in the 5-phase plans. This might be because the esophagus is highly mobile and often resides close to the target [41]; thus, the interplay effects might have increased the dose. In addition, we considered that since the mean absolute dose differences were 0.1 GyRBE for both techniques, the OAR doses in the SFUD and IMPT plans might not be signi cantly affected by the interplay effect.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In addition, a recent analysis of patients with stage III NSCLC showed that IMPT can significantly reduce radiation dose to the heart and lungs as compared to IMRT, which both influence EDIC and modeled OS2. 23 Additional studies are needed to more precisely model the association between EDIC, immune biomarkers, and survival outcomes to inform the selection of radiotherapy modality in UNSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, intensity-modulated PT (IMPT) has the potential to improve the conformality of the dose distributions when compared with conventional photon plans [ 12 ]. However, IMPT is also more affected by the influence of uncertainties due to breathing and anatomical changes, as argued by Boer et al [ 13 ]. In their prospective simulation study, the influence of such uncertainties on treatment delivery was thoroughly investigated.…”
mentioning
confidence: 99%